Actions of promotion and education for health: satisfaction of users of an institution dedicated to health promotion - Castro Pereira, Adriese; Souza Leite Campinas, Lúcia de Lourdes (O Mundo da Saúde, 2007)
SESC (Social Service of Commerce) is a private Brazilian institution created in 1946 by the commerce and services organization that maintain and administer it. SESC’s goal is the promotion of social well-being and the improvement of quality of life and cultural development of its users and the community as a whole. Since its creation the institution had a special care with the health of its users, focusing health positively for stimulating the prevention of diseases by inducing healthy behaviors and practices. Thus, SESC focus its planning to improve heath and quality of life. This article discuss the results of a research made with SESC users of the “Santo Amaro” unity aiming to identify the perception they have of activities related to health promotion planned by SESC. The results of the questionnaires applied indicate that in relation to personal life and health, a significant number of users declared to be satisfied, leading to the conclusion that the longer the use of SESC facilities and programs the greater the satisfaction of users related to their personal life and health. This research indicates that SESC as a health-promoting entity fulfills the declared commitment since its foundation to offering a diversified programming of health education favoring the adoption of habits that stimulate quality of life improvement.